Hispania, A journal devoted to the interests of the teaching of Spanish and Portuguese, Published by the American Association of Teachers of Spanish and Portuguese, Cincinnati, vol. 62, núms. 1, 2 y 3, 1979. - Gútemberg Bohórquez Cubides, Jesús (Thesavrvs, 2023)
Reseñas de revistas.